Kindergarten: Producer or Reducer of Inequality Regarding Physical Activity Levels of Preschool Children - Kippe, Karin Oddbjørg; Lagestad, Pål Arild (Frontiers in Public Health, 2018)
Several studies have shown that children have sub-optimal physical activity levels. Since preschool children (4–6 years-old) spend most of their time awake in kindergarten on weekdays, physical activity level at kindergarten is crucial. The study examines preschool children's physical activity level at kindergarten. Preschool children's activity level at kindergarten is also investigated related to activity level at leisure, gender, and mothers' education level, income, and age. Two hundred and forty four children (125 boys and 119 girls) supplied valid accelerometer data, and mothers' education level, income, and age were measured using a questionnaire. One-way ANOVA and linear regression were utilized as statistical analyses. The results demonstrated that physical activity level during kindergarten is the main contributor to preschool children's physical activity level on weekdays. Furthermore, boys were more active than girls, and preschool children's physical activity level at both leisure and at kindergarten were not associated with mothers' age, education level, or income. However, a positive association was found between physical activity level at leisure and physical activity level at kindergarten, in which physical activity level at kindergarten increases when physical activity level at leisure increases. Physical activity level was also significantly different between kindergartens. The study indicated that kindergartens increase inequality according to physical activity level among preschool children—contributing to creating differences according to low-active and high-active children.